An Australian National Compact – Something old, something new? - Butcher, John; Casey, J.; Dalton, B. (2012)
The Australian Labor Party (ALP) formed government under Prime Minister Kevin Rudd in 2007 promising to consult with the not-for-profit sector on the development of a national compact. It was the government’s aim to forge a new settlement with the sector after eleven years of Liberal/National Coalition government during which contractual governance rather than relational governance was the norm. The provenance of the National Compact, launched in March 2010, can be traced back to similar framework documents for inter-sectoral cooperation in the United Kingdom (principally, The Compact) and Canada (the Accord). The National Compact) cannot be explained solely in terms of policy diffusion or the predilection of centre-right political parties for policy instruments of this sort. Rather, explanation requires a more nuanced contextual analysis of the political and policy environment within which these frameworks emerged. In this article we compare the range of factors contributing to the development of The Compact (UK), the Accord) (Canada) and the National Compact (Australia). We apply a similar analysis to policy frameworks in selected Australian states. We conclude that compacts arrive on the policy agenda via the opening of policy windows and through the actions of policy entrepreneurs. Policy windows and the attention of policy entrepreneurs might be both contextual and therefore, time-limited. We consider the range of factors that appear to have a bearing on the impact and durability of inter-sectoral policy frameworks in each jurisdiction in order to draw tentative conclusions about the prospects for the Australian National Compact